2009
DOI: 10.1590/s0100-736x2009000700006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência para tuberculose caprina no semi-árido paraibano

Abstract: 526Pesq. Vet. Bras. 29(7): 526-532, julho 2009 RESUMO.-A tuberculose é uma enfermidade infecciosa, de distribuição mundial, provocada por micobactérias patogênicas, que afeta o homem e diversas espécies de mamíferos. Visando determinar a prevalência da Tuberculose Caprina e identificar fatores de risco associados à infecção foram tuberculinizados, através do Teste Tuberculínico Comparado (TCC), 1.866 caprinos de diferentes raças e idades, oriundas de 84 propriedades localizadas na microrregião de Monteiro, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
1
0
4
Order By: Relevance
“…According to data established by SILVA et al (2006), inconclusive reactions were not found in this study, Although there are no control and eradication programs for goat tuberculosis in the country, it is believed that the results occurred due to management type, with animals kept in open areas and with the possibility of interaction between different species. PIGNATA et al (2009), in the state of Paraíba, showed similar data, where 0.48% of goats submitted to comparative tuberculin test presented positive results. These authors attributed the prevalence, among other things, to the use of management without proper technical instructions.…”
Section: Resultssupporting
confidence: 54%
“…According to data established by SILVA et al (2006), inconclusive reactions were not found in this study, Although there are no control and eradication programs for goat tuberculosis in the country, it is believed that the results occurred due to management type, with animals kept in open areas and with the possibility of interaction between different species. PIGNATA et al (2009), in the state of Paraíba, showed similar data, where 0.48% of goats submitted to comparative tuberculin test presented positive results. These authors attributed the prevalence, among other things, to the use of management without proper technical instructions.…”
Section: Resultssupporting
confidence: 54%
“…Outra lesão frequente é a presença de células gigantes que foi encontrada em 21 linfonodos. Essas duas alterações são encontradas, também, na tuberculose, uma doença, provavelmente, de importância crescente nos rebanhos nacionais de caprinos (Pignata et al 2009), mas que aparentemente não tem sido diagnosticada em ovinos.…”
Section: Discussão E Conclusõesunclassified
“…No presente trabalho essa característica esteve presente em 47/96 das amostras avaliadas e causadas por C. pseudotuberculosis, E. coli, P. mirabilis, Pseudomonas aeruginosa, Trueperella pyogenes e Streptococcus spp. A mineralização e células gigantes são lesões, principalmente encontradas na tuberculose e LC (Pignata et al 2009, Souza et al 2011, sendo que nesta pesquisa foi possível identificar essas alterações nas amostras que foram isoladas E. coli, P. mirabilis, P. aeruginosa, Arcanobacterium pyogenes e Streptococcus spp. As lesões causadas por S. aureus não foi observado mineralização.…”
Section: Discussionunclassified
“…A LC é uma doença crônica, causada pela bactéria Corynebacterium pseudotuberculosis considerado o principal agente responsável por lesões abscedativas (Unanian et al 1985, Rosa et al 1989, Guedes et al 2007, Abreu et al 2008, Ribeiro et al 2011, Souza et al 2011, Andrade et al 2012, Valençoela et al 2012, Higino et al 2013, porém outras bactérias podem ser a causa dos abscessos, como Staphylococcus aureus, Escherichia coli, Streptococcus spp., Proteus mirabilis, Pseudomonas aeruginosa, Trueperella pyogenes e Mycobacterium tuberculosis (Rosa et al 1989, Pignata et al 2009, Benito-Peña et al 2010, Ribeiro et al 2011, Souza et al 2011, Andrade et al 2012, Valençoela et al 2012, Higino et al 2013.…”
unclassified